61.1k views
2 votes
What is the factored form of the expression?

d^2 = 36d + 324

User ABLX
by
4.7k points

1 Answer

3 votes

Answer:


(x-43.45)(x+7.45)=0

Explanation:

We have the quadratic equation
d^(2)=36d+324 i.e.
d^(2)-36d-324=0

As, the roots of the quadratic equation
ax^(2)+bx+c=0 are given by
x=\frac{-b\pm \sqrt{b^(2)-4ac}}{2a}.

So, from the given equation, we have,

a = 1, b = -36 , c = -324.

Substituting the values in
x=\frac{-b\pm \sqrt{b^(2)-4ac}}{2a}, we get,


x=\frac{36\pm \sqrt{(-36)^(2)-4* 1* (-324)}}{2* 1}

i.e.
x=(36\pm √(1296+1296))/(2)

i.e.
x=(36\pm √(2592))/(2)

i.e.
x=(36\pm 50.9)/(2)

i.e.
x=(36+50.9)/(2) and
x=(36-50.9)/(2)

i.e.
x=(86.9)/(2) and
x=(-14.9)/(2)

i.e. x = 43.45 and x = -7.45

Thus, the roots of the equation are 43.45 and -7.45.

Hence, the factored form of the given expression will be
(x-43.45)(x+7.45)=0

User PhantomSalt
by
5.2k points